A Dose–Response Study on the Relationship between White Meat Intake and Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) in Southern Italy: Results from the Nutrihep Study - Guido, Davide; Cerabino, Nicole; Di Chito, Martina; Donghia, Rossella; Randazzo, Cristiana; Bonfiglio, Caterina; Giannelli, Gianluigi; De Pergola, Giovanni (Nutrients, 2024)
(1) Background: Metabolic dysfunction-associated liver disease (MASLD) is one of the most important causes of liver disease worldwide. Meat consumption is a growing trend and white meat has been shown to have beneficial effects on cardiometabolic risk factors. The aim of this study was to investigate the dose–response relationship between white meat intake and MASLD at survey level in a Southern Italy setting. (2) Methods: This cross-sectional study encompassed 1192 subjects (509 males, 42.7%) without missing data from the second wave of the NUTRIHEP cohort (2014–2016). Adjusted dose–response modeling was employed for statistical analysis; (3) Results: There were 587 subjects with MASLD (49.2%), i.e., 278 males (54.6%) and 309 females (45.2%). By increasing the intake, an unfavorable influence of white meat on MASLD was significantly revealed in females, whereas a protective effect of white meat was detectable in males. Male sex was shown to be involved in other associations in this study, such as influencing the preference for specific foods such as poultry and chicken skin. (4) Conclusions: Our data suggest that white meat does not have a clear-cut independent dose–response effect on MASLD, but sex may be a trigger moderator for age and BMI, with an increasing unfavorable effect of white meat in women, and a favorable effect in men.